(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This research focuses on the influence of Rambu Solo on the life of the Muslim community in Tana Toraja. Rambu Solo is a funeral ceremony in Tana Toraja, South Sulawesi. This study aims to determine the positive and negative impacts of the Rambu Solo ceremony that occurs in Muslim communities in North Salubarani, Tana Toraja. This research is descriptive qualitative. The data obtained by using data collection techniques in the form of observation, interviews and documentation. Then the data was analyzed using a qualitative descriptive method. Qualitative descriptive method is to explain the phenomena that occur in the field. The results of this study indicate that Rambu Solo not only has a positive impact but also has a negative impact on the Muslim community in Tana Toraja. The positive impact is as an effort to preserve the ancestral culture of the Toraja people before and also as a place to strengthen family relations between communities and inter-religious relations. The negative impact of the Rambu Solo ceremony that occurs in the Muslim community in Tana Toraja is that it can take up free time, drain energy and can spend a lot of material if the person who performs the Rambu Solo ceremony is the closest family. From the results of this study, it can be concluded that the Rambu Solo ceremony can preserve ancestral culture as well as strengthen kinship relations and also strengthen family relations although it can take up free time, drain energy and materials that are not small in number for the needs of the party.